Proline and water stabilization of a universal two-step folding mechanism for β-turn formation in solution - Steinke, N; Genina, A; Gillams, R; Lorenz, C; McLain, S (American Chemical Society, 2018)
The atomic scale process by which proteins fold into their functional forms in aqueous solutions is still not well understood. While there is clearly an interplay between the sequence of the protein and the surrounding water solvent that leads to highly specific and reproducible folding in nature, there is still an ongoing debate concerning how water molecules aid in driving the folding process. By using a combination of techniques that provide information at the atomic level—neutron and X-ray diffraction and computer simulations—the mechanism of folding in a series of peptides that only vary with respect to the central side-chain residue has been determined. Specifically, β-turn formation for the KGXGK peptide (where X = P, G, S or L) occurs via a two-step water-driven attraction between specific sites on the peptide backbone. This proposed mechanism suggests that the site-specific hydration of the backbone facilitates the initial stages of protein folding and that this hydration interaction in combination with the presence of proline in the i + 1 position helps to stabilize the folded and intermediate folding state of the peptide in solution, leading to a greater propensity for PG containing sequences to occur in β-turns in proteins.